STRATEGI BAURAN PEMASARAN USAHA KECIL KERIPIK SINGKONG DI DESA BANDAR KHALIPAH KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Adisty Anggraini; Nisya Aulia; Nurjannah Nurjannah; Zainarti Zainarti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
A small cassava chip business is a household business that produces snacks made from special cassava snacks. The single most important factor influencing the performance of small businesses in Singapore is their marketing strategy, which takes into account their products, prices, promotions and distribution locations. This research was conducted in the small business community of Bandar Khalipah Village in Percut Sei Tuan district. The purpose of this study was to understand the mix marketing strategies used by the Singapore government. Descriptive qualitative, data collection techniques with notes, and documentation are the methods used for analysis. Research results 1) the marketing mix strategy used by small businesses in Singapore is a product made with good quality materials, good quantity, has a handle, and is wrapped in plastic. The quoted price is equal to the price. The traditional promotional method still used in Cassava Chips is